2D woven/ 3D orthogonal Woven Non-crimp E-glass Fabric as Reinforcement in Epoxy Composites using Vacuum Assisted Resin Infusion Molding. Issue 2 (June 2017) - Nayak, Suhas Yeshwant; Heckadka, Srinivas Shenoy; Sadanand, Ramakrishna Vikas; Bharadwaj, Kapil; Pokharna, Harsh Mukut; Sanjeev, Ananthakrishnan Rajaraman
E-glass/Epoxy composites were fabricated using Vacuum Assisted Resin Infusion Moulding (VARIM) in fiber weight fractions of 40%, 45%, 50% and 55 percent. E-glass fiber in the form of 2D plain woven fabric of 320 gsm and 3D orthogonal woven non-crimp fabric with 1830 gsm were considered for reinforcement. Mechanical properties including tensile strength, flexural strength, impact strength and inter-laminar shear strength (ILSS) of both the composites were evaluated and compared to explore the possibility of 3D fabric as an alternative over the plain weave fabric. Improvement in mechanical properties was seen with increase in fiber content in both the composites. Results support the view that 3D orthogonal weave fabric can be used in lieu of plain weave fabric as it exhibited improved mechanical properties. Morphological studies were used to analyze the fracture mechanisms.